2013
DOI: 10.4236/as.2013.411a003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological potential of soybean seeds treated with thiamethoxam and submitted to storage

Abstract: Bio-activators such as thiamethoxam have been used to increase the productive potential of plants, by means of metabolic and plant morphology modifications. Nevertheless, very little is known regarding the effectiveness of this insecticide when incorporated into lower quality level soybean seeds, particularly during storage. The objective of this work was to assess the influence of thiamethoxam on the physiological potential of soybean seeds with different initial vigor levels during four storage periods. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
2
18
2
Order By: Relevance
“…The results obtained for seed germination and the GRI indicated that all pesticides, except thiamethoxam, significantly reduced seed germination during storage of '97Y07RR' soybean seeds, in comparison with the control. However, Dan et al (2013) reported that thiamethoxam, applied at 90 days of storage, reduced seed vigor of ' Anta 82 RR' soybean. This shows that the tolerance of the genotype to the insecticide at different storage times is an intrinsic factor for seed vigor.…”
Section: Agroquímicos E Tempos De Armazenamento No Vigor De Sementes mentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained for seed germination and the GRI indicated that all pesticides, except thiamethoxam, significantly reduced seed germination during storage of '97Y07RR' soybean seeds, in comparison with the control. However, Dan et al (2013) reported that thiamethoxam, applied at 90 days of storage, reduced seed vigor of ' Anta 82 RR' soybean. This shows that the tolerance of the genotype to the insecticide at different storage times is an intrinsic factor for seed vigor.…”
Section: Agroquímicos E Tempos De Armazenamento No Vigor De Sementes mentioning
confidence: 99%
“…However, the environmental conditions of storage, without temperature and humidity control, as well as the application of pesticides on seeds, may reduce germination and seedling survival, due to potential phytotoxic effects (Dan et al, 2010(Dan et al, , 2013. It should be noted that pesticide use associated with a long storage period is also harmful to seed vigor (Krüger et al, 2016).…”
Section: Agroquímicos E Tempos De Armazenamento No Vigor De Sementes mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, Brzezinski et al (2015), evaluating the effect of anticipated treatment of soybean seeds with different combinations of chemical products, concluded that they damage crop performance. Likewise, Dan et al (2013) observed reduction in the emergence of seedlings derived from soybean seeds treated with the insecticide thiamethoxam after three months of storage.…”
Section: Introductionmentioning
confidence: 99%
“…Seed treatment with carbendazim + thiram + thiamethoxan, fludioxonil + metalaxyl-M + imidacloprid + thiodicarbe, fludioxonil + metalaxyl-M + thiamethoxan also reduced seed vigor compared to the control after 51 days of storage of the seeds (Table 3). Previous studies did not observe a negative effect of application of imidacloprid only (Castro et al, 2008;Dan et al, 2013Dan et al, , 2012, however, the association of imidacloprid + thiodicarb reduced vigor and germination of soybean seeds (Dan et al, 2012;Bortoletto et al, 2017). Sometimes when products are combined, there can be modification in some characteristics of the mixture that become more toxic to the seeds compared to the product alone.…”
Section: Physiological Quality Of Seedmentioning
confidence: 95%